IMPACT OF INSULIN AND MELATONIN ON HEPATIC ANATOMY, CELLULAR BIOCHEMISTRY, AND RECEPTOR EXPRESSION IN DIABETIC HEPATIC DAMAGE - Dr Bashir Ahmed Chandio; Dr Syed Faizan Ali Shah; Dr Abdullah Khilji; Dr Khalil Ahmed Sanghro (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives:                                                                                                               To examine the influence of exogenous melatonin and insulin on the biochemical, serological, histological, and receptor expression patterns within liver tissues following hepatic damage.Materials and Methods:  This observational study was conducted at Ghulam Muhammad Mahar Medical college Sukkur, Pakistan. We have enrolled 74 patients with DM. The study was conducted from July, 2023 to December, 2023. All patients enrolled underwent liver function test and lipid profile. The patients received a combination therapy involving melatonin and insulin. Blood samples were obtained from each participant and forwarded for laboratory analysis. The treatment's efficacy was documented by observing outcomes across all patients. Data collection utilized a predetermined questionnaire.Results: The mean age and BMI of the entire group of 74 patients were 49.17±9.42 years and 27.31±4.08 (kg/m²) respectively. Our analysis revealed elevated levels of ALT (765.14±154.8), AST (694.59±158.4), ALP (705.70±149.3), serum cholesterol (179.98±8.27), LDL (96.68±3.8), and VLDL (83.37±7.37), accompanied by a reduction in HDL levels (45.22±3.51). Based on Hepatic Anatomy, cirrhosis was observed in 16(21.6%), and fatty liver was observed in 16(21.6%) patients. Hepatic injury recovery was observed in 69 out of 74 cases (93.2%). Remarkable enhancements were detected in the biochemical profile, cellular structure of liver cells, and the expression pattern of MT1, MT2, and IR receptors, suggesting substantial recovery and restoration.Conclusion: It was concluded that the combined administration of melatonin and insulin among diabetic patients with hepatic injury yielded notably favorable outcomes in terms of effectiveness and disease recuperation.